2007
DOI: 10.1196/annals.1397.082
|View full text |Cite
|
Sign up to set email alerts
|

Release of β‐Amyloid from High‐Density Platelets

Abstract: The main component of Alzheimer's disease (AD) senile plaques in the brain is amyloid-beta peptide (Abeta), a proteolytic fragment of the amyloid precursor protein (APP). Platelets contain both APP and Abeta and much evidence suggests that these cells may represent a useful tool to study both amyloidogenic and nonamyloidogenic pathways of APP processing. It has been demonstrated that platelets activated by physiological agonists, such as thrombin and collagen, specifically secrete Abeta ending at residue 40. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…Apoptosis can contribute to disorders such as diabetes [13,14,15,16], tissue ischemia [17,18,19,20], bone fatigue [21], Alzheimer's disease [22,23,24,25,26,27,28,29,30,31,32], neurodegenerative disorders [33,34,35,36], plasticity associated with ischemic preconditioning [37], aging-related diseases [38,39,40], and toxic conditions during development [41,42]. The pathology with these disorders can be linked to mitochondrial dysfunction [43,44,45,46], especially during metabolic disorders [47] and Alzheimer’s disease [48], that ultimately can lead to cell death in a variety of cells such as neurons, endothelial cells (ECs), cardiomyocytes, and smooth muscle cells [32,49,50,51,52,53].…”
Section: Nicotinamide Oxidative Stress and Cellular Survivalmentioning
confidence: 99%
“…Apoptosis can contribute to disorders such as diabetes [13,14,15,16], tissue ischemia [17,18,19,20], bone fatigue [21], Alzheimer's disease [22,23,24,25,26,27,28,29,30,31,32], neurodegenerative disorders [33,34,35,36], plasticity associated with ischemic preconditioning [37], aging-related diseases [38,39,40], and toxic conditions during development [41,42]. The pathology with these disorders can be linked to mitochondrial dysfunction [43,44,45,46], especially during metabolic disorders [47] and Alzheimer’s disease [48], that ultimately can lead to cell death in a variety of cells such as neurons, endothelial cells (ECs), cardiomyocytes, and smooth muscle cells [32,49,50,51,52,53].…”
Section: Nicotinamide Oxidative Stress and Cellular Survivalmentioning
confidence: 99%
“…In fact, a recent study indicated that soluble Aβ can be internalized into lysosomes by the cerebrovascular smooth muscle cells, yielding Aβ deposits within the extracellular space of the vessel wall upon degeneration of smooth muscle cells. This is supposedly an important mechanism leading to cerebral amyloid angiopathy in AD [16] . Early studies by Di Luca et al [17] and Rosenberg et al [18] showed a reduction in the ratio between larger (120 to 130 kDa) and smaller (110 kDa) specimens of sAPP in platelets of patients with AD.…”
Section: Amyloid-related Markers In Plateletsmentioning
confidence: 99%
“…There is a growing consensus that changes in blood Aβ levels parallel AD onset and progression, although these findings remain discrepant with respect to specific species, that is, Aβ or Aβ 1-40 (2)(3)(4)(5)(6). Despite this discrepancy, evidence is now emerging in favor of the more pathologic form, Aβ , being elevated at the stage of mild cognitive impairment or an even earlier prodromal stage of AD, possibly owing to increased production (2,5,7).…”
Section: H I G H a β I N R E L A T I V E S O F A D P A T I E N T Smentioning
confidence: 99%